US government TARP bailout and bank lottery behavior - Del Viva, Luca; Kasanen, Eero; Saunders, Anthony; Trigeorgis, Lenos (Journal of Corporate Finance, 2021)
Considerable debate surrounds how the US government's TARP bailout intervention has affected the risk-taking and moral hazard behavior of U.S. banks around the global financial crisis. We examine this issue with a focus on lottery behavior introducing MAX/MIN as a new measure of lotteryness in banking to capture the loss protection from bank bailout guarantees. We find that the TARP bailout increased the likelihood of bank lotteryness and risk shifting. Lottery-like bank equities are riskier after TARP and exhibit fatter right to left tails. A consistent pattern of risk taking and lottery behavior extends both before and after the 2008–2009 crisis, engulfing the largest systemic banks (SIFIs). While confirming that lottery-like bank equities have lower short-term return, we find they exhibit better cumulative long-term return performance. Our findings have important policy implications regarding government intervention in banking crises.